The Legal Liability of the Roblox Gaming Platform as a Foreign Electronic System Operator for Child Protection in Indonesia - Amalia, Selma Dwi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid development of online gaming platforms such as Roblox has created a new digital environment widely accessed by children as a medium for recreation, social interaction, and creative exploration. However, the intensity of such usage also increases their exposure to various risks, including inappropriate content, online sexual exploitation, cyberbullying, and the leakage of children’s personal data. This study aims to analyze the legal responsibility of Roblox as a Foreign Private Electronic System Operator (PSE) within the Indonesian legal framework, particularly regarding child protection in digital spaces. This research employs a qualitative approach using a normative juridical method, combining the analysis of legal documents, sectoral regulations, government policies, and scholarly literature related to digital platform governance. The data sources include the Electronic Information and Transactions Law (UU ITE), the Child Protection Law, Government Regulation No. 71/2019, Government Regulation No. 17/2025 on Electronic System Governance for Child Protection, and Ministerial Regulation No. 2/2024 on Game Classification. The findings indicate that Roblox bears legal obligations to implement precautionary measures through age verification, content moderation, parental controls, risk detection systems, and the protection of children’s personal data.